2021
DOI: 10.1093/mnras/stab1351
|View full text |Cite
|
Sign up to set email alerts
|

The Gaia-ESO survey: a lithium depletion boundary age for NGC 2232

Abstract: Astrometry and photometry from Gaia and spectroscopic data from the Gaia-ESO Survey (GES) are used to identify the lithium depletion boundary (LDB) in the young cluster NGC 2232. A specialised spectral line analysis procedure was used to recover the signature of undepleted lithium in very low luminosity cluster members. An age of 38 ± 3 Myr is inferred by comparing the LDB location in absolute colour-magnitude diagrams (CMDs) with the predictions of standard models. This is more than twice the age derived from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…It provides stellar parameters, metallicity, and elemental abundances, radial velocities, and additional products, such as gravity index, chromospheric activity tracers, mass accretion rate diagnostics, and veiling. Several works in recent years have been devoted to the study of open clusters observed by the GES, among many we recall the latest ones: Bertelli Motta et al [76], Magrini et al [77,78,79], Prisinzano et al [80], Hatzidimitriou et al [81], Casali et al [82,83], Baratella et al [84], Randich et al [85], Jackson et al [86], Bonito et al [87], Gutiérrez Albarrán et al [88], Semenova et al [89], Binks et al [90]. In the following sections, we adopt the average abundances from IDR6 for the member stars of 57 clusters with ages ≥ 120 Myr published in Magrini et al [79].…”
Section: Gaia-esomentioning
confidence: 99%
“…It provides stellar parameters, metallicity, and elemental abundances, radial velocities, and additional products, such as gravity index, chromospheric activity tracers, mass accretion rate diagnostics, and veiling. Several works in recent years have been devoted to the study of open clusters observed by the GES, among many we recall the latest ones: Bertelli Motta et al [76], Magrini et al [77,78,79], Prisinzano et al [80], Hatzidimitriou et al [81], Casali et al [82,83], Baratella et al [84], Randich et al [85], Jackson et al [86], Bonito et al [87], Gutiérrez Albarrán et al [88], Semenova et al [89], Binks et al [90]. In the following sections, we adopt the average abundances from IDR6 for the member stars of 57 clusters with ages ≥ 120 Myr published in Magrini et al [79].…”
Section: Gaia-esomentioning
confidence: 99%
“…This uncertainty, which is of ≈ 10 to 20%, is comparable to the most accurate stellar evolutionary dating methods, i.e. isochrone fitting and lithium depletion boundary (Meynet et al 2009;Soderblom 2010;Jeffries et al 2013;Martín et al 2018;Binks et al 2021), but the morphological method is much easier to apply to a particular cluster or stream as it does not need stellar evolutionary models or dedicated spectroscopic observations. However, the role of possible systematic errors (e.g.…”
Section: Applications and Limitationsmentioning
confidence: 80%
“…In general, the lithium depletion boundary method provides older ages (by ≈ 50%) than isochrone fitting (e.g. Soderblom 2010;Binks et al 2021). The difference between these two dating methods is not restricted to the youngest clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Improved surveys for multiplicity, observational constraints on the initial conditions of pre-ms contraction, and a deeper understand-ing of the role of magnetic fields, rotation, and star spots in pre-ms evolution are needed to obtain robust ages and star formation histories in clouds and clusters (e.g. Binks et al 2021;Serna et al 2021;Cao et al 2022).…”
Section: Discussionmentioning
confidence: 99%